Chinese Economic Growth and Visitors to Japan: A Bivariate Cointegration Analysis - Kurasawa, Kazutaka (Asian Journal of Economic Modelling, 2016)
In recent years, Japan has experienced an unprecedented boom in foreign visitors, in particular from mainland China. Much of this boom has been driven by rising living standards in China. This paper studies the long-run relationship between Chinese economic growth and the number of visitors to Japan, using cointegration analysis. The Engle-Granger and the Phillips-Peron tests confirm that these variables are cointegrated. Ａ cointegrating equation and an error correction model are estimated to analyse the recent development of Chinese tourism demand and makes forecasts in the next several years. The cointegrating equation predicts that about 4.2 million Chinese travellers will visit Japan in 2020, up 64.0 percent from 2014. The error correction model indicates that about half of the recent surge of Chinese visitors is attributed to unexpected shocks and not a long-run trend.